Freeze-thaw stability of enzyme-treated cuchinta - Soriao, Ria Baltazar
ABSTRACT The study aimed to establish the stability of amylase-treated cuchinta exposed to 5 sequential freeze-thaw cycles. The most acceptable cuchinta was developed and subjected to various enzyme-treatments consisting of maltogenic alpha-amylase (0.005% and 0.012%) and pentosanase (0.003% and 0.005%). The most acceptable enzyme-treatment was determined through physicochemical and sensory analyses. The amylase-treated samples were subjected to 5 sequential freeze-thaw cycles and assessed through physicochemical, sensory and microbiological analyses. The most acceptable cuchinta formulation was achieved by lowering the water content and substituting brown sugar with white sugar of the original Peotraco (2007) recipe. The 0.012% maltogenic alpha-amylase was found most acceptable as it exhibited higher mean acceptance scores in chewiness and moistness. The pH and Aw of amylase-treated sample were similar to the other treatments while its compression value was significantly softer. Control and alpha-amylase treated samples were subjected to 5 sequential freeze-thaw cycles which involved 48h freezing at -18°C and 24h thawing at 12°C. As freeze-thaw cycles progressed, the net syneresis, pH and Aw of amylase-treated sample did not significantly change and the TPC, YMC and coliform count decreased. The TPC and coliform counts were within the safety guideline for microbiological quality. Alpha-amylase treated samples were still acceptable until freeze-thaw cycle 5 because the mean overall acceptability and textural attributes did not significantly change as freeze-thaw cycles progressed. The use of 0.012% maltogenic alpha-amylase was recommended for the commercial production of cuchinta because it brought improvement in textural characteristics and exhibited resistance to textural change until 5 freeze-thaw cycles.